Sales Analysis using Complex Networks: Communities and Centrality of Items - Hernández-González, Salvador (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4820 Sales in the cell phone and accessories area of a department store are analyzed with a complex network approach. Using measures of centrality and item grouping (communities), purchase ordering is shown, and the importance of each product is quantified. Sales are ordered by forming ‘communities’ around the cell phone chips. Based on the results, it can be concluded that cell phones are the most significant items of each community.